Effects of Zn content on the magnetic and magnetocaloric properties of Ni-Zn fenites - N, Chau (H. : ĐHQGHN, 2017)
Among spinel ferrites , Cd and Zn ferrites are always normal ferrites with Cd and Zn ions locating only in tetrahedral sites. This study presents effect of Zn on the magnetic and magnetocaloric properties of the mixed spinel ferrites.